(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
In this paper, preliminary studies of ten different plant extracts as potential corrosion inhibitors of carbon steel were examined. For each extract, the concentration range in which it shows anti-corrosion action was first determined, and then the most effective concentration was determined for each extract. The tests were performed in a brine solution saturated with CO2 at room temperature. The aim of this study was to isolate extracts with high effectiveness and subsequent electrochemical and surface methods to determine the mechanism of inhibitory action. For this purpose, potentiodynamic polarization was performed with Tafel extrapolation. Among all the tested extracts, lady’s mantle (92.17%) and dandelion root (95.07%) stood out with their effectiveness. Both tested extracts showed the behaviour of a mixed corrosion inhibitor with a dominant influence on the anode process.